JAPANESE-INDONESIAN IMPLICIT TRANSLATION OF ARTICLES 「日本のもてなし」IN THE QUARTERLY MAGAZINE にっぽにあDITION 39 YEAR 2006 - dance (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
To see how often words are implicit from Japanese into English, I looked at translations of Japanese articles and Indonesian in the title 「よこそ、もてなしの国へ」. The purpose of the study, is to assess how translators behave in Japanese language in Indonesian language, or vice versa. From the results of this assessment, it was found that there is a tendency to explicit persona pronouns in Indonesian more often than in Japanese. In addition, Indonesian texts give rise to cultural vocabulary that has no equivalent. It is important for translators to explore components to get matching results to match siurce languange.